Antioxidant and Antimicrobial Activities of Achyranthes Aspera from Ghodaghodi Lakeside, Kailali, Nepal - Awasthi, Harish; Shah, Pragati; Kunwor, Keshari; Kalauni, Surya Kant (Scholars' Journal, 2021)
Achyranthes aspera L. (Amaranthaceae) has long been used as antimicrobial, larvicidal, antioxidant and antidiabetic activities. The phytochemical screening of the methanolic extract of leaves and stems of Achyranthes aspera displayed the presence of almost all important phytochemical parameters. In the quantitative analysis of the plant, total phenolic content of methanolic and ethyl acetate extract of Achyranthes aspera plant was observed to be 362.74 ± 10.13 mg/g and 293.96 ± 11.77 mg/g GAE respectively. Total flavonoid in the methanolic and ethyl acetate extract of Achyranthes aspera was found to have 96.33 ± 7.67 mg/gm and 60.29 ± 5.98 mg/g QE. The methanolic extract of the plant extract of Achyranthes aspera exhibited high antioxidant activity among the plant extract (IC50 61.396 μg/ml). LC50 value of methanolic and ethyl acetate extract of the plant was identified to be 56.23 and 1158.77 μg/ml towards brine shrimp larvae respectively. The methanolic extract of Achyranthes aspera only active for Staphylococcus aureus and Bacillus subtilis.